2015
DOI: 10.1177/0333102415587704
|View full text |Cite
|
Sign up to set email alerts
|

International Classification of Headache Disorders 3rd edition beta-based field testing of vestibular migraine in China: Demographic, clinical characteristics, audiometric findings and diagnosis statues

Abstract: Our study showed that the clinical features of vestibular migraine in China were similar to those of Western studies. The definition of vertigo episodes and migraine subtypes of vestibular migraine in International Classification of Headache Disorders 3rd edition beta version might be modified further. More than five vertigo attacks per day within 72 hours might be helpful as far as identifying vestibular migraine patients with short-lasting attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 29 publications
(56 reference statements)
11
58
3
2
Order By: Relevance
“…However, the pathological mechanism requires further study. The duration of vertigo attacks in patients with VM ranged from seconds to days but seldom exceeded 72 h [14]. Our results regarding vestibular symptoms were partly divergent from those of previous studies.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, the pathological mechanism requires further study. The duration of vertigo attacks in patients with VM ranged from seconds to days but seldom exceeded 72 h [14]. Our results regarding vestibular symptoms were partly divergent from those of previous studies.…”
Section: Discussioncontrasting
confidence: 84%
“…Our previous study showed that vertigo attacks appeared on average 6 years after the onset of migraine in patients with VM and that vertigo attacks were always associated with migrainous headache in 34% and occasionally associated in 30%. Vertigo attacks had never occurred with migraine in 36% [14]. However, the pathological mechanism requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were examined by an experienced neurologist (JZ). A standardized neuro‐otology bedside assessment was performed as described previously . All patients performed a videonystagmography (VNG) test between the attacks.…”
Section: Methodsmentioning
confidence: 99%
“…Migraine affects 10–13% of the general population [1] and was ranked seventh in the 2010 Global Burden of Disease study [2]. In 36% of migraineurs, the migraine attack is preceded by a prodromal visual experience known as an aura [3]; migraine with aura (MA) is recognized as a specific migraine subtype.…”
Section: Introductionmentioning
confidence: 99%